Virtual Reality Technology in Analysis of the Sarek National Park Soundscape in Sweden - MŁYNARCZYK, Dorota; WICIAK, Jerzy (Archives of Acoustics, 2024)
The paper presents an in-depth analysis of the soundscape within Sarek National Park, the oldest national park in Europe, situated in Lapland, northern Sweden. The comprehensive acoustic measurements, ambisonic recordings, and 360° video recordings were carried out during a scientific expedition in the summer of 2020. The aim of the paper is to show the soundscape analysis of carefully selected characteristic locations in various parts of the valley. The paper extensively discusses the findings derived from the recorded data using both classical acoustic methods and the soundscape approach. The classic acoustic parameters, commonly employed in environmental acoustics as well as eco-acoustic indices such as: ACI (acoustic complexity index), ADI (acoustic diversity index), AEI (acoustic evenness index), NDSI (normalized difference soundscape index), BIO (energy level of biophony), amplitude index (M), and total entropy (H) were calculated. To gain further insights, listening tests, facilitated through virtual reality tools, were conducted, enabling participants to engage in soundwalk experiences. By employing a combination of traditional acoustic methods and innovative soundscape approaches, the paper presents a holistic evaluation of the auditory environment in Sarek National Park. The main contribution of the presented research is providing new data from the unique, geographically inaccessible region of the world, the Sarek National Park. This research not only enriches our understanding of the national park’s soundscape but also offers valuable insights into the interaction between the natural environment and human perception of sound.